LİSE ÖĞRENCİLERİNİN PSİKOLOJİK DAYANIKLILIK VE ÇATIŞMA ÇÖZME DAVRANIŞLARININ ÖZNEL İYİ OLUŞLARINI YORDAMASI. - AKDOĞAN, Bulut; YALÇIN, Süleyman Barbaros (Mehmet Akif Ersoy University Journal of Education Faculty, 2018)
In this study, it has been examined how Conflict Resolution Behavior and Psychological Resilience Level of high school students affect students' Level of Subjective Well-Being. The working group of the study totally consists of 548 students including in 313 girls and 235 boys who have continued their education at secondary educational institutions in the center of Kırıkkale in 2013-2014 academic year. In this study, to determine conflict resolution behavior "CRBIS-Conflict Resolution Behavior Identification Scale", to determine level of psychological resilience "APRS-Adolescent Psychological Resilience Scale" and to determine level of subjective well-being "ASWBSAdolescent Subjective Well-Being Scale" have been used. According to results obtained from the study, it has been seen that there is negative relationship between Adolescent Subjective Wellbeing and Aggression - the subscales of CRBIS whereas there is positive relationship at meaningful level between Adolescent Subject Well-being and Problem Solving. It has been found that relationship between the points of subscales of ASWBS and the point of subscales of APRC is positively and at meaningful level. It has been concluded that family support, pair support, school support, struggle determination and adaptation - the subscales of APRS and Problem Solving and Aggression Dimension - the subscales of CRBIS - are significant predictor of subjective well-being.